Nuevo registro del Águila Pescadora (Pandion haliaetus) para la provincia de Mendoza, Argentina - Pereyra Lobos, Roberto; Yacante, Ricardo (Nuestras Aves, 2008)
Este artículo no cuenta con un resumen.